Impact of STEM Education on Preschool Children's Scientific Process Skills - Ebru Deretarla Gül; Şule Kavak (e-Kafkas Eğitim Araştırmaları Dergisi)
This study was conducted to reveal the effect on scientific process skills of STEM activities. The study group consisted of 57 children, one experimental group, and two control groups. In this study, a semi-experimental research method was used. In the data collection process, three data tools were used to collect data. Two of them were developed by the researcher "Demographic Information Form," which contained personal information about children and their parents, and the "Scientific Process Skills Test" to evaluate the basic scientific process skills of 60-72-month-old children. developed by Goodenough in 1926, the "Good Enough Harris Test" was used to determine the homogeneous distribution of the research groups. In the analysis of the experimental process of this study, a 3x3 mixed design ANOVA method was used. To show the significant difference between the groups, parametric and nonparametric tests were used depending on whether they showed normal distribution or not. The study findings showed that the scientific process skills of the children who participated in the experimental group differed significantly from those of the children in the control groups. The findings obtained in this study suggest that STEM activities improve the basic scientific process skills of 60-72-month-old children.